Opinions of handball female players of different levels of performance about proffesionalism and handball status - Lovric, F.; Rogulj, N.; Herceg, Z. (Acta Kinesiologica, 2012)
The aim of this research was to determine variation in opinions of female handball players about motivation, engagement, commitment, dedication and accomplishments in handball, i.e. professionalism in handball, as well as opinions about characteristics and status of handball as a sport, among female handball players of different levels of performance. The research was conducted on the sample of 99 female handball players acting in the Premier League of Bosnia and Herzegovina. The correlation analysis indicated that, generally, there is no significant correlation between allegations contained in a questionnaire. After applying Kruskal-Wallis's test, statistically significant difference was noted in only two allegations on the basis of quality criteria determined by the average number of goals scored during the season. According to the results obtained we could conclude that female handball players have a similar approach to handball regardless of the level of their performance, i.e. their opinions about characteristics and status of handball as a sport, do not vary significantly